Epicardial adipose tissue in patients with systemic sclerosis - Wang, Xu; Butcher, Steele C; Myagmardorj, Rinchyenkhand; Liem; Sophie I E; Delgado, Victoria; Bax, Jeroen J; De Vries-Bouwstra; Jeska K; Marsan, Nina Ajmone (Oxford University Press, 2025)
Aims: Epicardial adipose tissue (EAT) has emerged as a mediator between systemic inflammatory disorders and cardiovascular disease, and may therefore play a role in the pathophysiology of cardiac involvement in systemic sclerosis (SSc). The aim of this study was to assess the correlation between EAT and left ventricular (LV) function, and to determine the prognostic value of EAT in patients with SSc.
Methods and results: Consecutive patients with SSc who underwent non-contrast thorax computed tomography and echocardiography were included. EAT mass was quantified using dedicated software. The study endpoint was all-cause mortality. A total of 230 SSc patients (age 53 ± 15 years, 14% male) were included. The median value of EAT mass was 67 g (interquartile range: 45-101 g). Patients with increased EAT mass (≥67 g) showed more impaired LV diastolic function as compared with patients with less EAT mass (<67 g), and even after adjusting for age and comorbidities, EAT mass was independently associated with LV diastolic function parameters. During a median follow-up of 8 years, 42 deaths occurred. Kaplan-Meier analysis showed that patients with increased EAT mass had higher all-cause mortality rate as compared with patients with less EAT mass (29% vs. 7%; P < 0.001). In the multivariable analysis, EAT was independently associated with all-cause mortality after adjusting for important covariates (HR: 1.006; 95% CI: 1.001-1.010).
Conclusion: In patients with SSc, EAT is independently associated with LV diastolic dysfunction and higher mortality rate.